Development of a real-time 3D simulation testbed for Cobot-AMR systems in manufacturing - Sheila Devi Suppiah (Nanyang Technological University, 2023)
Robotic systems have been on a rise and play a vital role for manufacturing shop floors to increase throughput and productivity. Have you ever wondered what goes into the pre-production planning stage for organisations planning to implement and deploy robotics and automation for their manufacturing plants? In this report, the use of multifaceted tasks involved in the development of a real-time 3D simulation testbed for one of Schaeffler’s manufacturing plants, will be explored. The report will cover mainly two tasks within the scope of the Final Year Project that involves the development of a controller script in C# that is designed to facilitate the articulation of the static Autonomous Guided Vehicles (AGVs) in the Unity simulation environment, as well as the utilisation of Virtual Reality (VR) interfaces along with Robot Operating System (ROS) and the MoveIt motion planning framework to enable the intuitive and immersive control of robotic systems to foster Human-Robot Collaboration (HRC). The research outcomes of the Final Year Project are also documented in the report, with emphasis on the potential of VR systems in the manufacturing space. However, the constraints to translate the efforts into physical deployment and the need for continued research to bridge the gap between simulation testbeds and practical manufacturing applications are also acknowledged.